2023
DOI: 10.1126/sciadv.adf3026
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia sensing requires H 2 S-dependent persulfidation of olfactory receptor 78

Abstract: Oxygen (O 2 ) sensing by the carotid body is critical for maintaining cardiorespiratory homeostasis during hypoxia. Hydrogen sulfide (H 2 S) signaling is implicated in carotid body activation by low O 2 . Here, we show that persulfidation of olfactory receptor 78 (Olfr78) by H 2 S is an integral component of carotid body activation by hypoxia. Hypoxia and H 2 S increased persulfidation in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“… 13 A report showed that redox modification of Olfr78 participates in carotid body activation by hypoxia to regulate breathing. 46 The results consistent with the above reports were observed in our study, the expression of Olfr78 was significantly decreased after hypoxic injury. In addition, some studies have shown that the release of inflammatory factors caused by NLRP3 inflammasome activation is a significant pathological feature of cardiovascular disease and brain injury.…”
Section: Discussionsupporting
confidence: 93%
“… 13 A report showed that redox modification of Olfr78 participates in carotid body activation by hypoxia to regulate breathing. 46 The results consistent with the above reports were observed in our study, the expression of Olfr78 was significantly decreased after hypoxic injury. In addition, some studies have shown that the release of inflammatory factors caused by NLRP3 inflammasome activation is a significant pathological feature of cardiovascular disease and brain injury.…”
Section: Discussionsupporting
confidence: 93%
“… 45 Mice with glomus cells deficient in adenylate cyclase 3, a key component of the olfactory signal transduction pathway, exhibit impaired cellular and breathing responses to hypoxia. 46 The physiological ligand(s) of Olfr78 is (are) unknown and the possibility that this G-protein-coupled receptor is constitutively activated 47 cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our analysis showed that Olfr59 (the rat equivalent to mouse Olfr78) gene was the only abundant Olfr member identified in the rat CB transcriptomic profile, highlighting the significance of G-protein signaling in different species. Peng et al [37] recently showed that redox modification of Olfr78 by H 2 S contributes to CB hypoxic sensing. In our study, Olfr59 gene expression increased significantly (> 2-fold) in adult CBs compared to neonates.…”
Section: Discussionmentioning
confidence: 99%